Immunization costs, from evidence to policy: Findings from a nationally representative costing study and policy translation effort in Tanzania. Issue 48 (10th November 2020) - Vaughan, Kelsey; Clarke-Deelder, Emma; Tani, Kassimu; Lyimo, Dafrossa; Mphuru, Alex; Manzi, Fatuma; Schütte, Carl; Ozaltin, Annette
Highlights: Delivery costs represent 33% of total immunization program costs in Tanzania. Costs are higher for outreach than for facility-based delivery. We used calibration methods to estimate unit and total costs. This work will inform domestic resource advocacy and planning. Abstract: Introduction: Information on the costs of routine immunization programs is needed for budgeting, planning, and domestic resource mobilization. This information is particularly important for countries such as Tanzania that are preparing to transition out of support from Gavi, the Vaccine Alliance. This study aimed to estimate the total and unit costs for of child immunization in Tanzania from July 2016 to June 2017 and make this evidence available to key stakeholders. Methods: We used an ingredients-based approach to collect routine immunization cost data from the facility, district, regional, and national levels. We collected data on the cost of vaccines as well as non-vaccine delivery costs. We estimated total and unit costs from a provider perspective for each level and overall, and examined how costs varied by delivery strategy, geographic area, and facility-level service delivery volume. An evidence-to-policy plan identified key opportunities and stakeholders to target to facilitate the use of results. Results: The total annual economic cost of the immunization program, inclusive of vaccines, was estimated to be US138 million (95% CI: 133, 144), or 4.32 (3.72, 4.98) per dose. The delivery costs made up 45 million (38, 52), or 1.38 (1.06, 1.70) per dose. The costs of facility-based delivery were similar in urban and rural areas, but the costs of outreach delivery were higher in rural areas than in urban areas. The facility-level delivery cost per dose decreased with the facility service delivery volume. Discussion: We estimated the costs of the routine immunization program in Tanzania, where no immunization costing study had been conducted for five years. These estimates can inform the program's budgeting and planning as Tanzania prepares to transition out of Gavi support. Next steps for evidence-to-policy translation have been identified, including technical support requirements for policy advocacy and planning.